(3GdeUfas - (3CHh HcQ YHO GdQRGb Hf geGe Hf fGaY GdMejQj GdUfYGfj Gdjefj, GdUfYGfj,J (B211 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH (B" (3GdQLd jNQL GdNTHI ef Mbg (B" (3gd jVef EPG CUGHJ EfSGfkG s
(3BNQgG (B:s
(3hjfJgi HBNQ GdcJGH s
(3ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B353s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B105 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1712s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdMOjK h GdeUWdMs